Degradação eletroquímica de efluentes contendo ácido cafeico usando eletrodo de diamante dopado com boro - Oliveira, Kaíque Souza Gonçalves Cordeiro (2019)
Coffee is one of the main global agribusiness products, however, the wet coffee processing industry is considered as being environmentally unfriendly due to its high consumption of water and large volumes of effluents generated. The wastewater obtained from this process is rich in phenolic compounds, such as caffeic and chlorogenic acids, which can be toxic and refractory to biological treatment. In this context, a study of electrooxidation of the model molecule caffeic acid (CA, 200 mg L-1) was carried out in an electrochemical flow reactor with boron-doped diamond electrode (BDD). The electrolyte volume used was 1.4 L containing 0.05 mol L-1 H2SO4 as supporting electrolyte. For this purpose, the effects of operational parameters such as α, which is related to current density, and flow velocity (u) on the: i) degradation and mineralization kinetics of CA; ii) kinetics of formation and oxidation of possible intermediates; iii) mineralization current efficiency (ε) and specific energy consumption (η), were investigated. The best results of mineralization (76% of TOC removal) and degradation kinetics (100% of removal) of the CA were obtained by applying the higher values of the studied variables (α = 1.2 and u = 1.11 m s-1), however, presenting a lower ε and higher η. The AC in solution was completely removed at the highest value of u, for all values of α studied. With the increase of α, there was an improvement in the rate of mineralization and oxidation of the organic matter, however, the time that the process operated under activated control was lower and thus, the ε was lower due to the parallel reactions; consequently, the η was higher. The increase in u provided an increase in mass transport coefficient, leading to an increase in the mineralization and oxidation rates of CA, as well as an increase in ε and a reduction in average specific energy consumption (ηG). The electrooxidation of CA on BDD electrode has led to the formation of formic, succinic and oxalic acids. The quantification of these intermediates was performed by high performance liquid chromatography. In a second step, the process was improved through the application of modulated current, which resulted in the reduction of η (from 256 to 52.4 kWh kg-1 TOC) due to the improvement in ε (from 17.9 to 77.1%). However, the process time also increased, from 7.1 to 12 h, when compared to the galvanostatic process. Finally, the application of modulated current in the electrochemical degradation of a real coffee processing wastewater was evaluated, revealing itself as an attractive alternative for farmers to treat in loco the low volume effluents.